2017
DOI: 10.1002/lno.10624
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen starvation reveal life‐cycle specific responses in the metabolome of Emiliania huxleyi (Haptophyta)

Abstract: The coccolithophore Emiliania huxleyi is a microalga with biogeochemical and biotechnological relevance, due to its high abundance in the ocean and its ability to form intricate calcium carbonate structures. Depletion of macronutrients in oceanic waters is very common and will likely enhance with advancing climate change. We present the first comprehensive metabolome study analyzing the effect of phosphorus (P) and nitrogen (N) starvation on the diploid and haploid life‐cycle stage, applying various metabolome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 128 publications
(256 reference statements)
3
44
5
1
Order By: Relevance
“…One of the original hypotheses for the DMSP mechanism was that DMSP replaces nitrogen‐containing osmolytes under NO 3 − limitation (Andreae, ). Although E. huxleyi is known to produce several N‐containing osmolytes (Gebser & Pohnert, ; Wordenweber et al , ), we found no evidence to support this hypothesis. Intracellular DMSP concentrations in E. huxleyi did not increase under NO 3 − limitation, in fact concentrations decreased slightly (Fig.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…One of the original hypotheses for the DMSP mechanism was that DMSP replaces nitrogen‐containing osmolytes under NO 3 − limitation (Andreae, ). Although E. huxleyi is known to produce several N‐containing osmolytes (Gebser & Pohnert, ; Wordenweber et al , ), we found no evidence to support this hypothesis. Intracellular DMSP concentrations in E. huxleyi did not increase under NO 3 − limitation, in fact concentrations decreased slightly (Fig.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous studies have demonstrated that growth at temperatures below the optimal growth temperature (T opt ) is metabolically balanced, with similar decreases in photosynthesis and respiration (Thomas et al, 2012;Baker et al, 2016;Barton et al, 2018). By contrast, growth at temperatures above T opt and under nutrient limitation (steadyor nonsteady-state) was linked to metabolic imbalances, in which photosynthesis and respiration are decoupled (Hockin et al, 2012;Baker et al, 2016;Wordenweber et al, 2018). The metabolic conditions of marine phytoplankton resulting from steady-state hyper-and hyposaline stresses are relatively unknown, as most previous studies have focused on euryhaline species or nonsteady-state responses to osmotic shock (Qasim et al, 1972;Macler, 1988;Jahnke & White, 2003;Bussard et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…DIC limitation, however, was not the trigger for entering stationary phase as POC production continued for several days after cessation of cell division. Wördenweber et al (2017) have recently shown that although the cell cycle is arrested by P starvation, enzymatic functionality is widely preserved. P starvation blocks the synthesis of DNA and membrane phospholipids, necessary for cell replication, arresting the cells in the G1 (assimilation) phase of the cell cycle (Müller et al, 2008).…”
Section: The Effect Of P Limitation On Carbon Productionmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology | www.frontiersin.org (Guarnieri et al, 2011(Guarnieri et al, , 2013Sibi et al, 2014;Li et al, 2015b;Ouyang et al, 2015;Henard et al, 2017;Zuñiga et al, 2018;Mocsai et al, 2019) Chloroidium sp. Katz et al, 2007;Jia et al, 2009Jia et al, , 2016Gu et al, 2014;Ge et al, 2016;Lv et al, 2016;Zhao et al, 2016;Wei et al, 2017b;Wang et al, 2019d Emiliana (Benner et al, 2013;Rokitta et al, 2014;Hunter et al, 2015;McKew et al, 2015;Wördenweber et al, 2018) Fistulifera solaris (JPCC Wang et al, 2004;Tran et al, 2009;Peled et al, 2011;Gu et al, 2014;Recht et al, 2014;Su et al, 2014;Gao et al, 2016;Baumeister et al, (Chen et al, 2014;Ge et al, 2014;Jungandreas et al, 2014;Rosenwasser et al, 2014;Yang et al, 2014;Abida et al, 2015;Alipanah et al, 2015;Feng et al, 2015;Bai et al, 2016;…”
Section: Metabolomics and Metabolic Modelsunclassified